2023
DOI: 10.1108/ijaim-02-2023-0035
|View full text |Cite
|
Sign up to set email alerts
|

Anti-corruption disclosure quality and earnings management in the United Kingdom: the role of audit quality

Abstract: Purpose Building upon institutional pressures on firms to deal with corruption, this study aims to investigate the association between a firm's engagement with anti-corruption disclosure quality (ACD_Q) and earnings management (EM). Also, this study examines the moderating role of audit quality in the association between ACD_Q and EM. Design/methodology/approach The authors constructed an ACD_Q index based on the 2010 UK Bribery Act and taking into account a wide range of rules on corruption and bribery, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…Previous studies have confirmed that a Big 4 audit firm (Deloitte, Ernst & Young, KPMG, and PricewaterhouseCoopers) is representative of high audit quality. The reason for this is that high audit quality status ensures high quality reporting earnings, in other words lower earnings management, see studies by Becker et al (1998), Krishnan (2003), Santos-Jaén, Martín de Almagro and Valls (2023), Sundkvist and Stenheim (2023), Salem et al (2023). In addition, Susak (2020) studied the impact of COVID-19 on earnings management and audit effect.…”
Section: The Context Of Earnings Management Of European Companies In ...mentioning
confidence: 99%
“…Previous studies have confirmed that a Big 4 audit firm (Deloitte, Ernst & Young, KPMG, and PricewaterhouseCoopers) is representative of high audit quality. The reason for this is that high audit quality status ensures high quality reporting earnings, in other words lower earnings management, see studies by Becker et al (1998), Krishnan (2003), Santos-Jaén, Martín de Almagro and Valls (2023), Sundkvist and Stenheim (2023), Salem et al (2023). In addition, Susak (2020) studied the impact of COVID-19 on earnings management and audit effect.…”
Section: The Context Of Earnings Management Of European Companies In ...mentioning
confidence: 99%
“…Previous research has shown that as the quality of audit work increases, the manipulation of financial results by audit firms decreases (Chi et al, 2011;Salem et al, 2023;Zgarni et al, 2016). At the same time, auditor independence is essential to ensure the quality of audits and protect stakeholder interests (Jamal & Sunder, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Earnings management (EM) is a strategy used within the limitations allowed by the Generally Accepted Accounting Principles (GAAP) to deliberately manipulate a company's financial reports so that the figures match a pre-determined target (Chang et al, 2022a;Palacios-Manzano et al, 2019;Santos-Jaén et al, 2021). EM is considered a latent threat and an undesirable practice in the economic-financial world (Dechow & Skinner, 2000;Teixeira & Rodrigues, 2022), and many accounting scandals in recent years have involved EM (Al-Absy et al, 2019;Salem et al, 2023). This has prompted widespread interest in reducing these unfair practices as much as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Due to information asymmetry, it could lead to managers' engagement in EM practices as the shareholders have insufficient motives, resources and access to relevant information to monitor the activities of the managers (Warfield et al, 1995). Hence, firms need to have a strong audit committee as they enable firms to restrain managers' opportunistic behaviour to engage in EM (Komal et al, 2022;Salem et al, 2023). Also, it helps firms to reduce the issue of information asymmetry, improving the overall FRQ (Bepari and Mollik, 2015).…”
Section: Introductionmentioning
confidence: 99%